Achievement emotions mediate the link between goal failure and goal revision: Evidence from digital learning environments. (June 2021) - Theobald, Maria; Breitwieser, Jasmin; Murayama, Kou; Brod, Garvin
Abstract: The present study tested how students emotionally react to and deal with goal failure. We (1) examined students' achievement emotions after they failed to achieve their learning goal and (2) tested whether students' achievement emotions after goal failure predicted goal revision. We tested medical students ( N = 344) who used a digital learning platform to prepare for a high-stakes exam. Students reported their learning goals (before studying) and their anger, tension, joy, and pride (after studying) each day over the course of 40 days. Daily goal achievement was assessed objectively via log-files. Multilevel analyses revealed that goal failure on a particular day predicted higher anger and tension and lower joy and pride. After goal failure, students generally down-regulated their goal the next day, and the more so the farther they had missed their goal. Achievement emotions mediated this link, however. Students who reported stronger negative emotions (i.e., more anger, less joy, and less pride) down-regulated their goals to a lesser extent. Together, results suggest that goal revision depends on previous goal achievement, but also on students' achievement emotions after goal failure. Highlights: Goal failure predicted more anger, more tension, less joy, and less pride. Students down-regulated their goals after goal failure – especially if they widely missed their goals. Achievement emotions mediated this link. Students down-regulated their goals to a lesser extent if they reported more anger, less joy, and less pride after failure. Goal revision likely depends on previous goal achievement but also on students' achievement emotions after goal failure.